Binomo Dalam Perspektif Ekonomi Syariah - Reva Rahayu; Nurlailiyah Aidatussholihah (International Conference on Islamic Economic (ICIE), 2024)
Buying and selling with digital techniques has now grown rapidly in the business world. The many online features that are disguised as investments by promising profits in a short time have made business people interested in these online features. The online feature that is currently popular is the trend in the Binomo Application which implements the Binary Option system. This article aims to analyze the contracts used in Binomo Trading whether they are in accordance with the principles of Islamic economics or in their transaction practices including platforms that contain speculation. The method in this research uses qualitative methods. This qualitative research is used to understand and explain social phenomena in depth, emphasizing meaning and context. The data sources obtained in this study come from literature that has to do with Binomo. The type of data taken uses qualitative data in the form of publication sources or written narratives. Data collection techniques use literature studies sourced from articles and journals related to Binomo. Data analysis techniques use descriptive analysis to describe the results of the research that has been studied. Based on the results of the discussion of this study, it shows that in the Binomo application in terms of its transaction practices contain elements of uncertainty, thus it has been confirmed regarding this practice according to contemporary fiqh that binary optionx trading, namely binaryx option transactions, has elements that contain speculation which is prohibited in Islam